Experimental and numerical analysis of underwater consolidation of dredged sediment: a case of study for the Marker Wadden - Barciela-Rial, Maria; van den Bosch, Barend A. P.; van Kessel, Thijs; Griffioen, Jasper; Winterwerp, Johan C. (Frontiers in Marine Science, 2024)
Dredged sediments, which are mud suspensions with concentrations exceeding the gelling point, are utilised in reclamation and Building with Nature projects. Beyond the gelling point, flocs occupy space and begin to form a network structure. This study investigates the impact of initial conditions, specifically the concentration above the gelling point and the stress state, on the consolidation of dredged sediment. The sediment from Lake Markermeer in the Netherlands was studied, specifically in the context of the construction of the Marker Wadden wetland. Material parameters were determined using two distinct experimental methods: settling columns and Seepage Induced Consolidation (SIC) tests. The differences observed between the two sets of material parameters suggest that the stress history and plastic deformation during mixing may influence the results. These effects were analysed using a one-dimensional vertical (1DV) consolidation model. The computed profiles were then compared with the profiles measured using an Ultrasonic High Concentration Meter. An initial concentration of 558.1 g/l, achieved by remixing the equilibrium profile of a normally consolidated suspension, resulted in larger final densities and a lower sediment-water interface. Conversely, a concentration of 175.6 g/l, achieved by remixing consolidating dredged sediment, yielded the same equilibrium layer thickness and density profile as virgin consolidation, albeit after a longer consolidation time. These findings are particularly relevant for land reclamation and wetland construction projects, where the initial density may be high and the dredging process’s mixing may alter the stress state.